2022
DOI: 10.5217/ir.2020.00158
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non-reaching of ileal pouch to the anus in laparoscopic restorative proctocolectomy with handsewn anastomosis for ulcerative colitis

Abstract: Background/Aims: Restorative proctocolectomy (RPC) with ileal pouch-anal anastomosis and handsewn anastomosis for ulcerative colitis requires pulling down of the ileal pouch into the pelvis, which can be technically challenging. We examined risk factors for the pouch not reaching the anus.Methods: Clinical records of 62 consecutive patients who were scheduled to undergo RPC with handsewn anastomosis at the University of Tokyo Hospital during 1989–2019 were reviewed. Risk factors for non-reaching were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…8 Similarly, we found patients who had 2 or more vessels divided had a median mobilization length of 20.4 cm. Although we could not evaluate the decision to change from an intended handsewn to a stapled anastomosis to increase length in this retrospective study, we did observe shorter mesenteric length and longer mobilization length associated with creation of a stapled anastomosis, consistent with the findings of Emoto et al 7 Finally, Poh et al did not see a statistical difference in ad-hoc CT indices analysis among their 21 nonreach events, which were 3:1 matched with an IPAA completion cohort. 4 Although not statistically significant, their nonreach subgroup did show a 0.9 cm shorter equivalent of mesenteric length and 1.4 cm longer mobilization length.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…8 Similarly, we found patients who had 2 or more vessels divided had a median mobilization length of 20.4 cm. Although we could not evaluate the decision to change from an intended handsewn to a stapled anastomosis to increase length in this retrospective study, we did observe shorter mesenteric length and longer mobilization length associated with creation of a stapled anastomosis, consistent with the findings of Emoto et al 7 Finally, Poh et al did not see a statistical difference in ad-hoc CT indices analysis among their 21 nonreach events, which were 3:1 matched with an IPAA completion cohort. 4 Although not statistically significant, their nonreach subgroup did show a 0.9 cm shorter equivalent of mesenteric length and 1.4 cm longer mobilization length.…”
Section: Discussionsupporting
confidence: 85%
“…A single institution study of laparoscopic IPAA found a distance from the terminal branch of the superior mesenteric artery (SMA) to the anal canal >11 cm on preoperative CT to be a risk factor for conversion to a stapled anastomosis, thereby lessening the required mesenteric length. 7 Another study using a similar methodology reported a terminal ileocolic artery to anal verge distance >21 cm and predicted the need to divide 3 or more mesenteric vessels to achieve adequate mesenteric length. 8 In this article, we use a methodology of CT-guided measurements of anatomic landmarks to predict nonreach before IPAA.…”
mentioning
confidence: 99%
“…However, proctocolectomy carries high risk of post-operative complications [20]. Ileal pouch anal anastomosis (IPAA) provides chance to save the anus of the patients who underwent proctocolectomy [21,22], and IPAA was possible 89% of UC patients in a Korean multicenter retrospective analysis [23].…”
Section: Surgical Treatment Of Dysplasia In Ucmentioning
confidence: 99%